استخدام نموذج القراءة التعاونية المتكاملة والتكوينية لتحسين مهارة القراءة لدى الطلاب: The Use of the Cooperative Integrated Reading and Composition Model to Improve Students' Reading Skills - Hidayati Nasution; Mahyudin Ritonga; Rindi Atika Ramadayani (Journal of Arabic Language Teaching, 2026)
The reliance on conventional, teacher-centred methods in Arabic reading instruction often leads to passive learning and low student motivation, thereby limiting proficiency development. While prior research acknowledges collaborative learning's benefits, its specific application through structured models like Cooperative Integrated Reading and Composition (CIRC) in Arabic Islamic junior high schools remains underexplored. This study aims to investigate the efficacy of the CIRC model in improving the Arabic reading skills of eighth-grade students. A quasi-experimental design with a non-equivalent control group was employed at Pemangku Islamic Junior High School, Bandung. The experimental group (n=35) was taught using CIRC, while the control group (n=32) received traditional rule-based instruction. Data from pre- and post-tests were analyzed for normality, homogeneity, and mean differences using paired T-tests and N-Gain scores. Results revealed a statistically significant improvement in the experimental group's reading scores (Mean N-Gain: 0.35; categorized as moderate effectiveness), with the experimental group outperforming the control group. The findings conclude that the CIRC model effectively enhances Arabic reading skills by promoting active, interactive, and socially constructed learning, offering a significant pedagogical innovation for similar educational contexts. إن الاعتماد على الأساليب التقليدية المتمركزة حول المعلم في تعليم القراءة باللغة العربية غالبًا ما يؤدي إلى تعلم سلبي وانخفاض دافعية الطلاب، مما يحد من تطوير كفاءاتهم. وعلى الرغم من أن الدراسات السابقة تعترف بفوائد التعلم التعاوني، إلا أن تطبيقه المحدد من خلال النماذج المنهجية مثل نموذج القراءة التعاونية المتكاملة والتكوينية في المدارس الإعدادية الإسلامية التي تدرس اللغة العربية لا يزال غير مستكشف بشكل كافٍ. تهدف هذه الدراسة إلى التحقيق في فعالية نموذج القراءة التعاونية المتكاملة والتكوينية في تحسين مهارات القراءة باللغة العربية لدى طلاب الصف الثامن. تم استخدام تصميم شبه تجريبي مع مجموعة ضابطة غير مكافئة في مدرسة المصباح المتوسطة الإسلامية بباندونج. دُرست المجموعة التجريبية (عددها 35 طالبًا) باستخدام نموذج القراءة التعاونية المتكاملة والتكوينية، بينما تلقت المجموعة الضابطة (عددها 32 طالبًا) تعليمًا تقليديًا قائمًا على القواعد. تم تحليل البيانات من الاختبارين القبلي والبعدي من حيث الطبيعي والتجانس وفروق المتوسطات باستخدام اختبار t المزدوج ودرجات N-Gain. أظهرت النتائج تحسنًا ذا دلالة إحصائية في درجات القراءة للمجموعة التجريبية (متوسط N-Gain: 0.35؛ ويُصنف ضمن الفعالية المتوسطة)، حيث تفوقت المجموعة التجريبية على المجموعة الضابطة. تستنتج الدراسة أن نموذج القراءة التعاونية المتكاملة والتكوينية يُحسن مهارة القراءة باللغة العربية بشكل فعال من خلال تعزيز التعلم النشط والتفاعلي والمنظور الاجتماعي، مما يوفر ابتكارًا تربويًا مهمًا للسياقات التعليمية المماثلة.